Manfaat Berkhotbah Ekspositori Bagi Para Pengkhotbah - Samuel, Selamet (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2023)
ABSTRACT A good sermon is determined by three things, namely the preacher, the preacher's preparation, and the anointing of the Holy Spirit. Besides, many people talk about the need for anointing, but not many people understand what anointing means. The author not only discusses good sermons, but also discusses the expository model of a good sermon, namely a sermon that is able to communicate Biblical ideas taken from correct interpretation, packaged in contemporary language, applied, and delivered with the power of the Holy Spirit. There are many ways to classify the form of expository preaching, both according to content, theme, and the length of the verse being preached.